2021
DOI: 10.1088/1742-6596/2110/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Turmeric Paper as an Indicator of The Borax Content in Crackers

Abstract: Borax is one of food additives that has been prohibited from being used by the Indonesian Government because it is dangerous to health. However, the fact is that borax has been widely added to several food products, such as skewered meatballs, school children’s snacks, bread, meatballs, tofu and crackers. Crackers containing borax is easily found in traditional markets. Short-term consumption of borax can cause various symptoms such as headache, fever, malaise, nausea or vomiting, pain in the upper abdomen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
0
1
Order By: Relevance
“…The results were also confirmed by the laboratory test on the associated crackers confirmed that the crackers were positive, i.e. those crackers indeed contain borax, therefore the turmeric paper was very suitable to be used as the first indicator of the borax content in food (Ermawati et al, 2021).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The results were also confirmed by the laboratory test on the associated crackers confirmed that the crackers were positive, i.e. those crackers indeed contain borax, therefore the turmeric paper was very suitable to be used as the first indicator of the borax content in food (Ermawati et al, 2021).…”
Section: Discussionmentioning
confidence: 54%
“…Prolonged consumption of boraxcontaminated foods can result in the accumulation of carcinogenic compounds in vital human organs like the liver, brain, kidneys, and testes. Ingesting high doses of borax can also manifest symptoms like stomach cramps, kidney impairment, and potentially fatal consequences if the toxicity level reaches 10-20 grams (Ermawati et al, 2021). Regulation stipulated by the Ministry of Health in Indonesia under the reference number 722/MenKes/per/IX/88 categorically prohibits the use of Borax as an additive in food products (Widiati & Wahyuningsih, 2023).…”
Section: The Health Implications Of Utilizing Formalin and Borax In F...mentioning
confidence: 99%
“…Berrocal et al (2004) mencionan en su investigación que para considerar una penetración como adecuada, el preservante debe haber alcanzado al menos la mitad del espesor de la pieza de madera tratada. Es decir que esta tonalidad es un indicador para determinar si la caña tiene un nivel alto de retención del preservante (Zaldívar et al, 2014) y las áreas que se encuentren impregnadas de este color reflejarán el nivel de penetración de la muestra (Ermawati et al, 2021). Como se observa en la figura 5, en ocho de las catorce muestras del estudio se evidenció la coloración deseada (T4, T5, T6 y T7), pero en la mayoría de los casos esta coloración no abarcaba todo el espesor de las muestras.…”
Section: Penetraciónunclassified